INFLUENCE OF BIG 5 PERSONALITY TRAITS ON THE INVESTMENT DECISIONS OF RETAIL INVESTORS-AN EMPIRICAL APPROACH - Dr. S. Uma Priyadharshini (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to analyze the behavioral aspects of retail investors through the identification of personality traits and the construction of a model to determine the extent of influence of the stated factors. Emotions are pervasive and predictable drivers of decision making. The dynamic nature of human beings necessitates the analysis of how emotional factors impact the decision-making process. The study used empirical research methodology and hence a larger sample size was chosen (454 samples) and both primary and secondary sources of information were used extensively. For the Structural Equation Model (SEM), AMOS 18.0 version was used. Reliability and validity tools were utilized to analyze the model fit. The personality traits considered for the study are extraversion, agreeableness, conscientiousness, neuroticism and openness. A human being may not exclusively fall into one particular personality trait. An attempt was made to quantify the impact of the different personality traits on the investment decisions. The output showed that the model is fit and all the parameters fell within the accepted range of the model fit indices. Further, the study has provided empirical evidence to prove that the personality trait of conscientiousness has a significant influence on the investment decision making process of retail investors. The implication and recommendations based on this finding are discussed. The impact of social conditioning factors, behavioral bias, herd behavior, environment of upbringing, moral values of investor, religious values of investor in affecting the investment decisions could be analyzed as there is a paucity of research in these areas.